Framing UNRWA’s Visual Content on Instagram for Humanitarian and Relief Aid during the First 100 Days of War in Gaza - Moharam, Mohammed Mostafa Refaat (Dirasat: Human and Social Sciences, 2025)
Objectives: This study examines the framing of visual content on United Nations Relief and Works Agency for Palestine Refugees’ (UNRWA) official Instagram account during the first 100 days of the Israeli war on Gaza. The analysis aims to explore the relationship between the visuals and UNRWA’s humanitarian and relief efforts for Palestinians. Methods: The study covers the period from October 7, 2023, to January 15, 2024 and employs a content analysis approach based on media framing theory. The study relies on both qualitative and quantitative content analysis methods. Results: The study concludes that photos were the most prevalent form of content, with News/Feature Photos depicting destruction and aid at the forefront. UNRWA also relied on videos featuring their officials engaging with international media channels, such as CNN, Al Jazeera, and the BBC. Camera angles, shot sizes, and lighting choices effectively conveyed the emotional impact of the conflict, with a particular focus on vulnerable groups, such as children, women and the elderly, to highlight the humanitarian crisis. Conclusions: The visual content predominantly focused on three main themes: "Destruction," "Providing humanitarian aid," and "Human interests." The "Destruction" frame emphasized the extent of Palestinian casualties, displacement, the spread of diseases and famine. The "Providing humanitarian aid" frame highlighted the importance of relief efforts, including medical care and logistical support. The "Human interests" frame portrayed the experiences and daily routine of affected individuals, particularly children and the elderly.